"Orthogonal‐Twisted‐Arm" Ligands for The Construction of Metal–Organic Frameworks (MOFs): New Topology and Catalytic Reactivity. Issue 69 (3rd November 2020) - Zhao, Kai; He, Ying; Shan, Chuan; Ren, Junyu; Wojtas, Lukasz; Wang, Li; Li, Guanghua; Song, Zhiguang; Shi, Xiaodong
Abstract: Extended tetratopic benzoic acid ligands with "orthogonal‐twisted‐arms" conformations were designed and synthesized for the construction of new MOF structures (OTA‐MOF). Upon coordination with Cd 2+ and Cu 2+ cations, two well‐defined new MOFs were prepared. X‐ray single crystal structures were successfully obtained, demonstrating the formation of a new topology (4, 4, 4‐c). The OTA2‐MOF‐Cu gave moderate stability in organic solvents and good gas sorption ability toward CO2 . This new MOF showed superior catalytic reactivity toward the epoxide‐CO2 cycloaddition, giving >50 folds yield enhancement over the controlled reaction without MOF. It is expected that this new ligand design, porous structure, and excellent CO2 catalytic reactivity will make OTA‐MOF promising new materials for applications in catalysis and separation. Abstract : New topology : Extended tetratopic benzoic acid ligands with "orthogonal‐twisted‐arms" conformations were designed and synthesized for the construction of new MOF structures (OTA‐MOF). X‐ray single crystal structures were successfully obtained, demonstrating the formation of a new topology (4, 4, 4‐c). The OTA2‐MOF‐Cu gave moderate stability in organic solvents and good gas‐sorption ability towards CO2 .